Potential Associations Between Microbiome and COVID-19 - Wang, Huifen; Wang, Haiyu; Sun, Ying; Ren, Zhigang; Zhu, Weiwei; Li, Ang; Cui, Guangying (Frontiers in Medicine, 2021)
The COVID-19 pandemic caused by coronavirus (SARS-CoV-2) has plunged the world into a major crisis. It is characterized by strong infectivity, high morbidity and high mortality. So far, it is still spreading in some countries. Microbiota and their metabolites affect human physiological health and diseases by participating in host digestion and nutrition, promoting metabolic function, regulating immune system, and so on. Studies have shown that human microecology is associated with many diseases, including COVID-19. Here, we first reviewed the microbial characteristics of COVID-19 from the aspects of intestinal microecology, pulmonary microorganisms and oral microorganisms. Then we summarized the possible microecological mechanisms involving in the progression of COVID-19. Fecal bacteria transplantation (FMT) and probiotics may play a positive role in the treatment of COVID-19 and reducing the fatal consequences of the disease.